In defence of safer spaces: Punk, privilege and safer spaces policies. (1st February 2020) - Lucy Hill, Rosemary; Megson, Molly
Increasing attention to the prevalence of sexual harassment at live music events has led to the adoption of safer spaces policies by venues and promoters. Punk's politics of inclusion and equality suggest that such policies would be welcome as a means to promote access for marginalized groups. However, safer spaces policies are sometimes controversial and their content and implementation patchy. Such policies therefore bear closer examination in order to understand their value and meaning for punk politics. Here we examine the use of safer spaces policies in punk and DIY music spaces asking, how is safety conceptualized, for what purpose, and who benefits from them? We draw on a discourse analysis of safer spaces policies and interviews with punks about sexual violence at gigs. We argue that safer spaces policies can be a valuable tool for promoting access to pleasurable experiences whilst lessening the fear of discrimination, harassment and violence. However, safer spaces can also continue to privilege already privileged punks. We conclude that when safer spaces policies are implemented they must go hand in hand with practical measures to enable inclusion. In doing so the needs of marginalized groups must be prioritized.